Monetary Policy and its Impact on Wealth Inequality : A Study of Post-2008 United States - Stamenic, Marko (2025)
The thesis investigates the impact of monetary policy on wealth inequality in the United States from 2008-2023. Using the Federal Funds Rate and the Federal Reserve’s balance sheet as key monetary policy tools, and the transmission channels of interest rates, asset price dynamics, labour markets and inflation, the analysis aims to capture individual effects on wealth distribution. A time series regression analysis is employed using Ordinary Least Squares on two measures of inequality, including the Gini coefficient and the top 1% wealth share to capture both overall distribution and the concentration at the very top. Robustness is ensured by addressing data specific challenges. The results of the analysis demonstrate the importance of addressing distributional effects in policy making, finding a significant link between interest rate adjustments and quantitative easing with wealth inequality. Rising house prices are strongly tied to reductions in inequality across both models, while stock market performance showed mixed effects. Inflation is associated with higher overall inequality, although its effect on top 1% wealth share is insignificant. Unemployment on the other hand, reduces the top 1% wealth share but does not exhibit a significant relationship with broader inequality. The findings confirm that monetary policy has distinct distributional consequences, influencing wealth dynamics in asymmetrical ways across the population.